The Reversible Non-covalent Aggregation Into Fibers of PGLa and Magainin 2 Preserves Their Antimicrobial Activity and Synergism - Juhl, Dennis Wilkens; Glattard, Elise; Lointier, Morane; Bampilis, Panos; Bechinger, Burkhard (Frontiers in Cellular and Infection Microbiology, 2020)
Magainin 2 and PGLa are antimicrobial peptides found together in frog skin secretions. When added as a mixture they show an order of magnitude increase in antibacterial activity and in model membrane permeation assays. Here we demonstrate that both peptides can form fibers with beta-sheet/turn signature in ATR-FTIR- and CD-spectroscopic analyses, but with different morphologies in EM images. Whereas fiber formation results in acute reduction of the antimicrobial activity of the individual peptides, the synergistic enhancement of activity remains for the equimolar mixture of PGLa and magainin 2 also after fibril formation. The biological significance and potential applications of such supramolecular aggregates are discussed.